Magnetic resonance findings in a Cavalier King Charles spaniel with osteopetrosis, Chiari‐like malformation and syringomyelia. Issue 1 (17th March 2019) - Fernandes, Ricardo; Jordan, C J; Driver, Colin
Abstract : Osteopetrosis (OP) is a rare genetic condition characterised by osteoclast impairment, deficient bone remodelling and increased bone density. Human patients with OP often present with fractures, osteomyelitis, anaemia, abnormal skeletal development, cranial nerve compression and rarely increased intracranial pressure secondary to craniosynostosis and/or calvarial thickening. A 17‐month‐old male neutered Cavalier King Charles spaniel was presented for evaluation of occasional painful vocalisation. MR of the brain and the vertebral column revealed a rare association of Chiari‐like malformation (CLM) and calvarial thickening due to diffuse OP resulting in severe cerebellar compression and herniation into the foramen magnum. To the authors' knowledge, this report represents the first described case of calvarial thickening caused by OP in association with CLM and syringomyelia in veterinary medicine.